2004
DOI: 10.1073/pnas.0306239101
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline inhibits contusion-triggered mitochondrial cytochrome c release and mitigates functional deficits after spinal cord injury

Abstract: We investigated whether permeability transition-mediated release of mitochondrial cytochrome c is a potential therapeutic target for treating acute spinal cord injury (SCI). Based on previous reports, minocycline, a second-generation tetracycline, exerts neuroprotection partially by inhibiting mitochondrial cytochrome c release and reactive microgliosis. We first evaluated cytochrome c release at the injury epicenter after a T10 contusive SCI in rats. Cytochrome c release peaked at Ϸ4 -8 h postinjury. A dose-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
188
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 307 publications
(195 citation statements)
references
References 51 publications
6
188
0
1
Order By: Relevance
“…Teng et al . (2004) have shown that spinal cord injury (SCI) increases mitochondrial cytochrome c release and minocycline treatment provides neuroprotective effect by reducing cytochrome c release in SCI. These data suggest that therapeutic regulation of mitochondrial function may be an effective approach to treat neurotrauma.…”
Section: Discussionmentioning
confidence: 99%
“…Teng et al . (2004) have shown that spinal cord injury (SCI) increases mitochondrial cytochrome c release and minocycline treatment provides neuroprotective effect by reducing cytochrome c release in SCI. These data suggest that therapeutic regulation of mitochondrial function may be an effective approach to treat neurotrauma.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies reported the potential use of MC as a cytoprotectant in the treatment of several neurological disorders including amyotropic lateral scerosis [2], multiple sclerosis [3], Alzheimer's disease [4], Huntigton's disease [5], Leber's hereditary optic neuropathy [6], and Parkinson's disease (PD) [7][8][9]. Furthermore, neuroprotective potency of MC has been observed in experimental models of acute cerebral ischemia [10,11], spinal cord- [12][13][14] and traumatic brain injury [15]. But, also contradictory and even detrimental effects of MC were reported recently [16][17][18][19][20], pointing at the importance of a thorough understanding of the detailed cellular and molecular mechanisms triggered by MC.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, numerous therapeutic strategies have been tested to increase post-SCI OL survival. Several studies have shown that the anti-inflammatory agent minocycline promotes white matter sparing and OL protection after SCI, in part by inhibiting microglial production of pro-NGF [146][147][148]. Lee et al [149] showed that methylprednisolone, a common treatment after SCI, protected OLs, but not neurons by blocking apoptosis.…”
Section: Safeguarding Oligodendrocytesmentioning
confidence: 99%